METER, FEEL, AND PHRASING IN WEST AFRICAN BELL PATTERNS: THE EXAMPLE OF ASANTE KETE FROM GHANA - Paulding, Ben (International Library of African Music, 2017)
This article offers an analysis of west African bell patterns, positioning them as an entry to musical analysis of west African drumming. How can bell patterns be used as a tool by researchers to establish meter? What information do they provide about the "feel” of the music? And finally, how do these patterns interact with the underlying meter and feel, and what does this reveal about phrasing in west African music? To answer these questions, this article examines the case of the dawuro iron bell in Asante Kete drumming from Ghana. A close analysis of the Kete dawuro bell pattern reveals that the Kete pattern may be represented in an "African 12/8” or ternary-quadruple meter, emphasizes the importance of the half-time 2-feel embodying the Asante maxim of "not hurrying”, and demonstrates the highly motile and "goal-oriented” phrasing exemplified in Kete's timeline patterns. To the broader west African and diasporic scholarly communities, this article presents a model for inferring meter, feel, and phrasing through close analysis of west African bell patterns.
Keywords: Music theory; West African Music; Phrasing (Music); Bell Pattern; Timeline; Ghana; Meter (Music); Feel (Music); African Music